Femoral Stem Fracture and Successful Reimplantation Using Femoral Window Technique in Canine Cemented Total Hip Replacement: Case Report - Degórska, Beata; Sterna, Jacek; Kalwas-Śliwińska, Magdalena (Frontiers in Veterinary Science, 2021)
The fractured stem is a very rare, late complication in total hip replacement procedure in dogs. Here, we present one case after cemented total hip replacement with successful reimplantation, including clinical signs and radiographic findings. Four year- old, male, golden retriever was presented with lameness of left hind limb two years after cemented hip prosthesis. Based on clinical examination and clinical signs and x-ray femoral stem fracture was identified. Well visible stem fracture in the midshaft with bone remodeling and a gap between the cement mantle and the stem was shown on lateral x-ray view. The dog underwent reimplantation of the cemented stem using the same size of the implant.